2018
DOI: 10.17219/acem/81607
|View full text |Cite
|
Sign up to set email alerts
|

The effect of silver nanoparticles on the reproductive system of adult male rats: A morphological, histological and DNA integrity study

Abstract: Background. Silver nanoparticles (AgNPs) are more often used in various products, and consequently the potential deleterious effects associated with exposure to them are of concern. Several lines of evidence have demonstrated that the toxicity of AgNPs affects different organs and leads to some side effects, including weight loss, inflammation and cell death. Objectives. The aim of this study was to evaluate the effect of different concentrations of AgNPs on sperm parameters and testicular histology. Material … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 23 publications
3
20
0
Order By: Relevance
“…The seminiferous tubule morphometric analysis showed that all the tubular parameters evaluated significantly reduced in the AgNPs-D7 group, whereas no difference was found between AgNPs-D14, D28, and D56 and Control groups. Similar results reported by Fathi et al (2018), showed that an intraperitoneal injection of AgNPs (125 mg/kg) caused a significant reduction in the diameter, area and circumference of seminiferous tubules. In contrast, increased diameter, area and circumference of seminiferous tubules in animals treated with AgNPs were observed by Gromadzka-Ostrowska et al (2012).…”
Section: Discussionsupporting
confidence: 88%
“…The seminiferous tubule morphometric analysis showed that all the tubular parameters evaluated significantly reduced in the AgNPs-D7 group, whereas no difference was found between AgNPs-D14, D28, and D56 and Control groups. Similar results reported by Fathi et al (2018), showed that an intraperitoneal injection of AgNPs (125 mg/kg) caused a significant reduction in the diameter, area and circumference of seminiferous tubules. In contrast, increased diameter, area and circumference of seminiferous tubules in animals treated with AgNPs were observed by Gromadzka-Ostrowska et al (2012).…”
Section: Discussionsupporting
confidence: 88%
“…Other studies further corroborated these effects. Fathi et al () showed the noxious effects of silver nanoparticles on the sperm and seminiferous tubules, while Qin et al () stated that cerium oxide nanoparticles adversely affected testosterone levels with a concomitant depletion of mRNA expression in steroidogenic‐related genes. Furthermore, Hou and Zhu () suggested that nanoparticles could elicit various stress responses in reproductive organs via the mechanisms of oxidative stress, apoptosis and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies confirmed that the reproductive toxicities of AgNPs are achieved by increasing inflammation, disrupting DNA structure, down-regulating gene expression, decreasing mitochondrial function, inducing ROS production and apoptosis. These toxicities of AgNPs to the reproductive system are size-, time- and dose-dependent 347 , 348 . Zhang et al 347 investigated the effects of AgNPs with different sizes (10 nm and 20 nm) on male somatic Leydig cells and Sertoli cells, and found that cell viability was inhibited by AgNPs in size- and concentration-dependent manners.…”
Section: Potential Toxicity Of Agnpsmentioning
confidence: 99%